A novel hedgehog inhibitor for the treatment of hematological malignancies. Issue 10 (November 2018) - Lin, Peng; He, Yuanming; Chen, Guodong; Ma, Haikuo; Zheng, Jiyue; Zhang, Zubin; Cao, Biyin; Zhang, Hongjian; Zhang, Xiaohu; Mao, Xinliang
Abstract : The hedgehog-smoothened (HH/SMO) pathway has been proposed as a potential therapeutic target for hematological malignancies. Our previous studies designed a series of HH inhibitors with novel scaffolds distinctive from vismodegib, the first Food and Drug Administration-approved HH inhibitor for the treatment of basal-cell carcinoma and medulloblastoma. In the present study, we evaluated these HH inhibitors against blood cancers and found that HH78 displayed potent activity in suppressing the HH signaling pathway. HH78 competitively bound to SMO and suppressed the transcriptional activity of GLI by the luciferase reporter gene assay and the measurement of HH/SMO-downregulated genes, including cyclin D2, cyclin E, PTCH1, PTCH2, and GLI. HH78 at low micromolar concentrations induced significant cancer cell apoptosis showed by increased caspase-3 activation, annexin V-staining and downregulated prosurvival proteins, including c-Myc, Bcl-2, Mcl-1, and Bcl-xL. In contrast, vismodegib did not show any effects on these apoptotic events. HH78 also suppressed the activation of the AKT/mTOR pathway, which cross-talks with the HH/SMO pathway. Finally, HH78 inhibited the growth of human leukemia K562 in nude mice xenografts with no overt toxicity. Collectively, the present study identified a novel HH inhibitor with great potential for the treatment of hematological malignancies.